2020
DOI: 10.1002/fft2.43
|View full text |Cite
|
Sign up to set email alerts
|

Maillard conjugates and their potential in food and nutritional industries: A review

Abstract: Maillard reaction (MR) is a cascade of complex interactions between reducing sugars and amine groups in food processing and storage. It produces a variety of volatile compound, nonenzymatic intermediates, and high molecular weight melanoidin contributing improved aroma, color, flavor, and antioxidant properties to the final food products. When uncontrolled, it can produce some harmful derivatives such as acrylamide, heterocyclic amine, advanced glycation end Products (AGEs), and other substances that can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 183 publications
(144 reference statements)
0
20
0
Order By: Relevance
“…Briefly, whole longan fruits were dried in a hot air dryer using a drying condition of Honeyqueen Co., Ltd. (Lamphun, Thailand), with the final requirements for the pulp: 14-17% moisture content and about 0.5-0.6 water activity (a w ) according to Thai agricultural standard (TAS [27]. Then, 500 g dried whole longan (control sample) were incubated at 60 C in desiccators previously equilibrated at~75% relative humidity (NaCl saturated solution) with aging time of 5,10,15,20,25,30,40, and 50 days. The treated samples were peeled and seeded to obtain only the pulp.…”
Section: Preparation Of Black Dried Longan Pulp (Bdlp) and Bdlp Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, whole longan fruits were dried in a hot air dryer using a drying condition of Honeyqueen Co., Ltd. (Lamphun, Thailand), with the final requirements for the pulp: 14-17% moisture content and about 0.5-0.6 water activity (a w ) according to Thai agricultural standard (TAS [27]. Then, 500 g dried whole longan (control sample) were incubated at 60 C in desiccators previously equilibrated at~75% relative humidity (NaCl saturated solution) with aging time of 5,10,15,20,25,30,40, and 50 days. The treated samples were peeled and seeded to obtain only the pulp.…”
Section: Preparation Of Black Dried Longan Pulp (Bdlp) and Bdlp Extractmentioning
confidence: 99%
“…The Maillard reaction products (MRPs) and/ or the SPC of dried fruit products are exhibited during manufacturing, warehousing and shipping of the product [2,3]. The Maillard conjugates in early stage or the SPC and melanoidin are provided with sensory characteristics, which can be utilized in food products for color, flavor, and taste improvement [9,10,11]. Moreover, the SPC could effectively enhance the antioxidant, antitumor, antihypertensive, and immune-stimulating activities through in vitro techniques [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, more than 30 HAAs have been identified in various foods. Several epidemiological studies indicated that the frequent intake of thermally processed foodstuffs containing HAAs may lead to an increased risk of human cancers, such as colon, prostate, and mammary cancers ( Alaejos and Afonso, 2011 , Cao et al, 2020 , Liu et al, 2020 , Xu et al, 2021 ). The International Agency for Research on Cancer (IARC) has thus classified IQ as a probable (class 2A) human carcinogen and PhIP, MeIQx, and MeIQ as possible (class 2B) human carcinogens ( IARC, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maillard, reported a reaction between glucose and glycine upon heating resulting in the formation of brown pigments [4]. Later the covalent bonds formed between carbohydrates and proteins during heating in a non-enzymatic browning reaction was named the Maillard reaction [5] [6]. Glycation is a part of the Maillard reaction, or browning of food, during cooking which enhances the taste, color, and aroma of the food to make it more palatable [4] [7].…”
Section: Introductionmentioning
confidence: 99%